Impact of norepinephrine versus phenylephrine on brain circulation, organ blood flow and tissue oxygenation in anaesthetised patients with brain tumours: study protocol for a randomised controlled trial - Faisal Mohamad, Niwar; Koch, Klaus Ulrik; Aanerud, Joel; Meier, Kaare; Mikkelsen, Irene Klærke; Espelund, Ulrick S; Eriksen, Christian Fenger; Juul, Niels; Alstrup, Karen Baden; Jespersen, Bo; Fries, Lene Marie; Tankisi, Alp; et al. (BMJ open, 2025)
IntroductionVasopressor support is often preferred as an efficient and convenient way to raise the blood pressure during surgery and intensive care therapy. However, the optimal vasopressor for ensuring organ blood flow and tissue oxygen delivery during surgery remains undetermined. This study aims to assess the impact of norepinephrine versus phenylephrine on cerebral and non-cerebral organ perfusion and oxygenation during anaesthesia in neurosurgical patients with brain tumours. The study also explores the impact of the vasopressor agents on the distribution of cardiac output between various organs.Methods and analysisThis is an investigator-initiated, double-blinded, randomised clinical trial including 32 patients scheduled for supratentorial brain tumour surgery. The patients are randomised to receive a phenylephrine or norepinephrine infusion during preoperative positron emission tomography (PET) examinations and the following neurosurgical procedure. PET measurements of blood flow and oxygen metabolism in the brain and other organs are performed on the awake subject during anaesthesia, following a 10% and 20% gradual increase in blood pressure from the baseline value. The primary endpoint is the between-group difference in cerebral blood flow. Secondary endpoints include detection of ischaemic brain lesions possibly associated with vasopressor treatment, changes in cerebral oxygen metabolism, non-cerebral organ blood flow and oxygen metabolism, cardiac output, regional cerebral oxygen saturation, autoregulation and distribution of cardiac output between organs.Ethics and disseminationThis study was approved by the Danish National Medical Ethics Committee (20 May 2022; 2203674). Results will be disseminated via peer-reviewed publication and presentation at international conferences.Trial registration numberEudraCT no: 2021-006168-26. ClinicalTrials.gov: NCT06083948.